Pendidikan Multikultural: Menuju Kesatuan Melalui Keanekaragaman - Gusnia Fatimah Azzahra; Masduki Asbari; Annisa Shintya Ariani (Journal of Information Systems and Management (JISMA), 2023)
Multicultural education has become a crucial cornerstone in shaping a diverse and cohesive society today. The objective of this study is to explore and analyze the role of multicultural education in culturally diverse communities, backgrounds, and identities. This report utilizes a qualitative descriptive method with note-taking as the data collection technique, as the data source involves listening to oral narratives from the YouTube channel "Bukalapak," titled "Multicultural Education: Breaking Down the Boundaries," presented by the speaker Ai Nurhidayat. The study's findings elucidate that an approach toward unity through multicultural education can cultivate a sense in each individual to accept, appreciate, accommodate, and protect existing diversity. Multicultural education has effectively influenced society to become more open to differences.